Battling Voices: Schizophrenia as Social Relation in Abel García Roure’s Una cierta verdad [A Certain Truth] (2008) - Fraser, Benjamin (Disability Studies Quarterly, 2016)
Director Abel García Roure studied filmmaking with Joaquim Jordà at the Universitat Pompeu Fabra de Barcelona, and this, his first long-form cinematic product, is a highly nuanced documentary prioritizing the interplay between the film's two privileged groups: providers and patients. The battle of voices we watch unfold on screen is a social dialogue between these two polarized groups of actors. The potential resolution of this conflict—in this Global Disability Studies reading of García Roure's film—seemingly lies outside of the clinical institutions into which we are drawn along with these necessarily social actors. This article linked the content and form of the film through an analysis that bridges its social and spatial context, previous Disability Studies work on Spanish cultural production, and the writings of Michel Foucault. Ultimately, the film suggests that it is the clinical paradigm's low tolerance for nuance and lack of precise tools that in fact perpetuates this ongoing battle of voices. The resulting picture emphasizes schizophrenia as a cognitive disability that must be understood simultaneously as a social relation.